(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
Identity formation and development has been a fundamental goal of the all-around educational work from children’s very early age. The importance of a curriculum founded on a value system in which identity as a value occupies one of the most significant places has been recognized in the Croatian national curriculum at all levels, especially in early and pre-school education and in the primary school. In the development of identity, literature plays a particular role, encouraging the reader to identify with the characters, and then to assume their attitudes, values, behaviour - in short, to imitate the identities of literary heroes. The paper acknowledges the importance of the Croatian children’s novel, which, by its rich identity distribution, becomes an encouragement and inspiration to young readers.